Evaluation of rigid-end offset effect on seismic behavior of a structure subjected to Van earthquake - Bekiroglu, Serkan; Sahin, Abdurrahman; Sevim, Baris; Ayvaz, Yusuf (TECHNO-PRESS, 2013)
Numerical damage assessment of Van train station building consisting of three RC blocks due to 2011 Van Earthquakes by nonlinear dynamic analysis is presented. The structural model is created with rigid-end offsets and plastic hinges for nonlinear analysis. Rigid-end offsets are considered for connection areas and proposed for wall-supported elements. In wall-supported elements, walls take place in a limited part of the columns. Nonlinear dynamic analysis of the building with and without rigid-end offsets is performed by using real earthquake records and results are compared. The results show that rigid-end offsets have significant effects on the seismic behavior of the structures.
Keywords: rigid-end offset; wall-supported elements; plastic hinge; nonlinear time history analysis; STEEL FRAMES; PART II; Engineering